Multi-Omics Reveals Inhibitory Effect of Baicalein on Non-Alcoholic Fatty Liver Disease in Mice - Li, Ping; Hu, Jianran; Zhao, Hongmei; Feng, Jing; Chai, Baofeng (Frontiers in Pharmacology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease, whose etiology is poorly understood. Accumulating evidence indicates that gut microbiota plays an important role in the occurrence and progression of various human diseases, including NAFLD. In this study, NAFLD mouse models were established by feeding high fat diet (HFD). Baicalein, a natural flavonoid with multiple biological activities, was administered by gavage, and its protective effect on NAFLD was analyzed by histopathological and blood factor analysis. Gut microbiota analysis demonstrated that baicalein could remodel the overall structure of the gut microbiota from NAFLD model mice, especially Anaerotruncus, Lachnoclostridium and Mucispirillum. Transcriptomic analysis showed baicalein restored the expressions of numerous genes that were upregulated in hepatocytes of NAFLD mice, such as Apoa4, Pla2g12a, Elovl7, Slc27a4, Hilpda, Fabp4, Vldlr, Gpld1 and Apom. Metabolomics analysis proved that baicalein mainly regulated the processes associated with lipid metabolism, such as alpha-Linolenic acid, 2-Oxocarboxylic acid, Pantothenate and CoA biosynthesis and Bile secretion. Multi-omics analysis revealed that numerous gens regulated by baicalein were significantly correlated with pathways related to lipid metabolism and biosynthesis and secrection of bile acid, and baicalein might affect lipid metabolism in liver via regulating the ecological structure of gut microbiota in NAFLD mice. Our results elucidated the correlated network among diet, gut microbiota, metabolomic and transcriptomic profiles in liver. This knowledge may help explore novel therapeutic approaches against NAFLD.